2021
DOI: 10.15446/profile.v23n2.89212
|View full text |Cite
|
Sign up to set email alerts
|

Pedagogical Practicum and Student-Teachers Discursively Conceived in an ELT Undergraduate Program

Abstract: The research study shows how pedagogical practicum is conceived, and how student-teachers are constructed as language teachers, within the discourses spoken in the initial meetings and institutional documents of pedagogical practicum in an English language teaching undergraduate program in Bogota, Colombia. The discourses were analyzed under the principles of ethnography of communication and linguistic ethnography. This study affords insights into a contributory conception of pedagogical practicum and into an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…The teaching practicum (TP) is an opportunity for student-teachers to develop disciplinary self-efficacy (see, Lucero & Cortés-Ibañez, 2021;Martins et al, 2015). This view has permeated initial teacher Education programs worldwide to the extent that TP has been thought to be the space in which student-teachers learn to be language teachers (Freeman, 2002).…”
Section: Teaching Practicummentioning
confidence: 99%
“…The teaching practicum (TP) is an opportunity for student-teachers to develop disciplinary self-efficacy (see, Lucero & Cortés-Ibañez, 2021;Martins et al, 2015). This view has permeated initial teacher Education programs worldwide to the extent that TP has been thought to be the space in which student-teachers learn to be language teachers (Freeman, 2002).…”
Section: Teaching Practicummentioning
confidence: 99%
“…Secondly, the practicum is not only a process for student-teachers to develop the knowledge and teaching skills that they have acquired throughout their major (Castañeda-Trujillo & Aguirre-Hernández, 2018;Chaves-Varón, 2008;Esteban-Núñez, 2021) but also a process to gain research experience by implementing a small-scale research project (Castellanos-Jaimes, 2013;Fandiño-Parra, 2013;Ríos-Beltrán, 2018). Thirdly, the practicum is an experience to learn about how to be a teacher in real situations and contexts and from their practicum advisors' or cooperating teachers' advice (Cote-Parra, 2012;Esteve, 1998;Lucero & Cortés-Ibañez, 2021). For these three views, the practicum represents the practical knowledge generated by studentteachers because of their everyday experimentation and continuous reflection inside and outside the classroom.…”
Section: The Practicum In the Colombian Elt Scholarshipmentioning
confidence: 99%
“…Other local studies have initially shown that student-teachers seem to be embodied practitioners with knowledge, beliefs, emotions, attitudes, interests, and roles (Aguirre-Sánchez, 2014;Carvajal & Duarte-Medina, 2020;Castañeda-Trujillo & Aguirre-Hernández, 2018;Castellanos-Jaimes, 2013;Lucero & Cortés-Ibañez, 2021;Lucero & Roncancio-Castellanos, 2019;Olaya & Gómez-Rodríguez, 2013;Suárez-Flórez & Basto-Basto, 2017). Even though these studies serve as initial references to understand how student-teachers are conceived in the local ELT field, a deeper exploration of how the Colombian scholarship sees both student-teachers and the practicum within ELT undergraduate programs is necessary.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The researchers found that the reflection levels are primarily technical and very uncritical due to the different dynamics that are handled within the teaching practicum and the degree of commitment to their own professional development. Also, Lucero and Cortés-Ibañez (2021) continued their exploration of pre-service English teachers in the teaching practicum, but this time they focused on the discursive level. They analyzed conversations in meetings and institutional documents that showed how the teaching practicum is a space in which identity as an English teacher is consolidated.…”
Section: Impact On Other Studies In Colombiamentioning
confidence: 99%